Effects of Moringa Oleifera Lam. Leaf Extracts On the Histology of Paracetamol Induced Hepatotoxicity in Rats (Journal of Chittagong Medical College Teachers' Association, 2017)
This study was designed to evaluate the Hepatoprotective effect of extract of Moringa oleifera Lam. leafon the Histology of the liver of albino rats. Thirty (30) adult albino rats were divided into five (5) groups. Group 1 was the Control group that received distilled water for 7 days, group 2 was the vehicle control group that received single dose of 2 ml of propylene glycol and group 3 received single dose of Paracetamol (2gm/kg ), Group 4 recieved only extract of Moringa oleifera Lam. leaffor 7 days and Group 5 was pre-treated with 500 mg/kg of the ethanolic plant extract of Moringa oleifera for 7 days and before inducing the liver damage on the 7th day with 2gm/kg of paracetamol. On the 9th day rats were sacrificed and the liver was fixed immediately in Formalin. The liver tissues was processed and stained in Haematoxylin and Eosin (H&E). The histological observations showed that the plant extract of Moringa oleifera Lam. prevent liver damage.JCMCTA 2016 ; 27 (2) : 44 - 49